EFFECT OF TEMPERATURE AND CULTURE MEDIA ON MYCELIAL GROWTH AND SPORULATION OF Botryotinia ricini CAUSING GRAY MOLD OF CASTOR - C. SARADA, R. ARUTSELVAN , G. UMA DEVI, R.D. PRASAD and (The Journal of Research, PJTSAU, 2020)
Gray mold diseases of castor caused by the fungus Botryotinia ricini is responsible for disease epidemics and heavy yield losses in castor growing regions of Telangana state. A laboratory experiment was conducted to study the mycelial growth rate, colony character and sporulation pattern of Botryotinia ricini on ten different culture media viz., corn meal agar, pikovskayas agar, carrot agar, potato carrot agar, glucose agar, oat meal agar, potato dextrose agar, czapek’sdox agar, soybean meal agar and water agar. The mycelial colony diameter, culture characteristics (texture, pigmentation, and pattern) and sporulation of B.ricini were greatly influenced across the culture media tested. OMA and PDA evinced higher mycelial growth and sporulation of B. ricini, whereas remaining eight media revealed low sporulation. Colony colour varied from grayish-white to brown across the culture media tested. Findings revealed that oat meal agar was the most suitable culture medium for growth and sporulation of B. ricini. The optimum temperature for its growth and sporulation was found to be 22oC under in vitro conditions.